2019
DOI: 10.1155/2019/7021428
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Overexpression for the Protective Effect of Skin-Derived Precursors against UV-Induced Damage: Evidence from a Three-Dimensional Skin Model

Abstract: Background Skin photodamage is associated with ultraviolet- (UV-) induced reactive oxygen species (ROS) overproduction and nuclear factor erythroid 2-related factor 2 (Nrf2) inactivation. In our previous study, skin-derived precursors (SKPs) were shown to ameliorate a UV-induced damage in mice, probably through Nrf2 activation and ROS scavenging. Objective To clarify the mechanism underlying the photoprotective effect of SKPs against UV-induced damage in a three-dimensional (3D) skin model. Methods The Nrf2 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…Cells and tissues in a hyperglycemic environment induce the generation of ROS, promote inflammatory response, and delay wound healing [ 30 ]. NRF2 prevents oxidative stress and regulates the production of related antioxidant enzymes, such as SOD1, GPx, heme oxygenase 1 (HO-1), and catalase [ 31 , 32 ]. The results of this study also confirmed that rutin increases the production of antioxidant enzymes SOD1 and GPx by upregulating the expression of NRF2 ( Figure 6 A).…”
Section: Discussionmentioning
confidence: 99%
“…Cells and tissues in a hyperglycemic environment induce the generation of ROS, promote inflammatory response, and delay wound healing [ 30 ]. NRF2 prevents oxidative stress and regulates the production of related antioxidant enzymes, such as SOD1, GPx, heme oxygenase 1 (HO-1), and catalase [ 31 , 32 ]. The results of this study also confirmed that rutin increases the production of antioxidant enzymes SOD1 and GPx by upregulating the expression of NRF2 ( Figure 6 A).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the inhibition of the NFκB transcription system, the phytonutrient combinations resulted in a synergistic activation of the ARE/Nrf2 transcription system. UV-induced ROS generation is a major mechanism through which UV causes detrimental effects on skin [ 32 ] and, thus, activation of ARE/Nrf2 is one of the basic mechanisms to balance UV-induced skin damage, as was shown in a 3D skin model injected with Nrf2 over-expressing skin-derived precursor cells [ 33 ]. The inhibition of NFκB and activation of ARE/Nrf2 by various carotenoids and polyphenols was previously shown in several publications [ 22 , 26 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been well known that endogenous antioxidant enzymes, such as SODs, GPx, and CAT, scavenge ROS [ 31 ]. Recently, Xian et al (2019) have reported that UV irradiation significantly elevates the level of ROS, however, nuclear factor erythroid 2-related factor 2 (Nrf2) overexpression in the skin-derived precursors (SKP) significantly ameliorates UV-induced damage in mice via the remarkable elevation of SOD, CAT, GPx, and reduced glutathione mRNA and protein levels, through Nrf2/HO-1 and PI3K/Akt pathways in a three-dimensional skin model [ 32 ]. In addition, it has been reported that the anti-photoaging effects of natural antioxidants, such as sinapic acid [ 33 ] and juglanin [ 34 ], are mediated by decrease of ROS generation and increases of SOD1, SOD2, CAT, GPx, and Nrf2 gene expression levels in UVB irradiation-damaged HaCaT keratinocytes.…”
Section: Discussionmentioning
confidence: 99%